2012
DOI: 10.1038/jid.2012.184
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding the Psoriasis Disease Profile: Interrogation of the Skin and Serum of Patients with Moderate-to-Severe Psoriasis

Abstract: Psoriasis is a complex disease with an expanding definition of its pathological features. We sought to expand/refine the psoriasis transcriptome using 85 paired lesional and non-lesional samples from a cohort of patients with moderate-to-severe psoriasis vulgaris who were not receiving active psoriasis therapy. This new analysis identified 4,175 probe sets (representing 2,725 unique known genes) as being differentially expressed in psoriasis lesions compared with matched biopsies of non-lesional skin when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
251
4
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(274 citation statements)
references
References 37 publications
17
251
4
2
Order By: Relevance
“…This cytokine expression pattern is similar to the inflammatory response in human psoriatic plaques and therefore validates the CD18 hypo PL/J psoriasis model (44,45). Although skin gd T cells have previously been reported to primarily produce IL-17, our IF analyses of CD18 hypo PL/J skin sections convincingly demonstrated that dermal gd T cells significantly contributed to IL-17, IL-22, and TNF-a production.…”
Section: Discussionsupporting
confidence: 83%
“…This cytokine expression pattern is similar to the inflammatory response in human psoriatic plaques and therefore validates the CD18 hypo PL/J psoriasis model (44,45). Although skin gd T cells have previously been reported to primarily produce IL-17, our IF analyses of CD18 hypo PL/J skin sections convincingly demonstrated that dermal gd T cells significantly contributed to IL-17, IL-22, and TNF-a production.…”
Section: Discussionsupporting
confidence: 83%
“…While GRHL3 was similarly expressed between normal and uninvolved psoriasis skin, it was found to be consistently and significantly upregulated 2.62-fold in psoriasis lesions in 3 independent datasets ( Figure 3, A and B, and refs. [31][32][33]. Intriguingly, patients with stronger upregulation of GRHL3 expression (lesional versus uninvolved) also showed stronger upregulation of genes induced by IL-17 and IL-22 (P ≤ 1 × 10 -10 and P ≤ 3.03 × 10 -5 , respectively; Figure 3C, Supplemental Table 1, and ref.…”
Section: Grhl3 Is Dispensable For Homeostatic Adult Epidermal Barriermentioning
confidence: 97%
“…To begin investigating the above hypothesis, we compared our prior GRHL3 siRNA knockdown gene expression and GRHL3 ChIP-Seq datasets from normal differentiating human keratinocytes (NHEK) (35) with the human psoriasis gene expression data (31)(32)(33). Of the 1,206 GRHL3-regulated genes in differentiating NHEKs, 312 were also differentially expressed in human psoriasis lesions compared with nonlesional skin (overlap significant, P ≤ 3.65 × 10 -5 ; Figure 3D and Supplemental Figure 5A).…”
Section: Grhl3 Is Dispensable For Homeostatic Adult Epidermal Barriermentioning
confidence: 99%
“…The recent finding that patients with psoriasis show an overexpression in lesional skin of mRNA from genes linked to cardiovascular risk (e.g. inflammatory mediators and renin), corresponding to increased levels of the relevant proteins in the serum, is highly suggestive in this regard (88).…”
Section: The Relationship Between Psoriasis and Other Imidsmentioning
confidence: 99%